TREATMENT OF FLUORIDE BEARING CONTAMINATED WATER USING SIMULTANEOUS ADSORPTION AND BIODEGRADATION IN A LABORATORY SCALE UP: FLOW BIO-COLUMN REACTOR BY JAVA PLUM SEED - Singh, Tej Pratap; Ghosh, Sanjoy; Cb, Majumder (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Here, we aimed for the treatment of fluoride bearing contaminated water using simultaneous adsorption and biodegradation in a biocolumn reactor by using java plum seed. Methods: We immobilized Acinetobacter baumannii bacteria on the java plum seed in the bio-column reactor. The water used contained a sample of fluoride with concentration of 20 mg/L. The bed depth service time design model and empty bed residence time were used to analyze the performance the bio-column. We examined and observed closely the effect of different operating parameters such as flow rate of bed depth and initial concentration on this simplified bio-column reactor design model. Desorption experiment was conducted to evaluate the possibilities of regeneration and to reutilize of media. Results: We observed that the bio-column reactor is capable to reduce the concentration of the pollutants in the effluent water below their permissible limit. Reduction in DO along the bed height of the reactor was also observed, which supports the aerobic nature of the bacteria. Conclusion: The experimental results were encouraging and indicate that java plum (Syzygium cumini) seed is a feasible option to use as a biosorbent to remove fluoride in the bio-column reactor. Keywords: Bio-reactor, Simultaneous adsorption and biodegradation, Flow rate, Acinetobacter baumannii MTCC 11451, Physicochemical adsorption, Bed depth service time, Empty bed residence time.